2014
DOI: 10.1377/hlthaff.2013.0743
|View full text |Cite
|
Sign up to set email alerts
|

Adults In The Income Range For The Affordable Care Act’s Medicaid Expansion Are Healthier Than Pre-ACA Enrollees

Abstract: The Affordable Care Act (ACA) has dramatically increased the number of low-income nonelderly adults eligible for Medicaid. Starting in 2014, states can elect to cover individuals and families with modified adjusted gross incomes below a threshold of 133 percent of federal poverty guidelines, with a 5 percent income disregard. We used simulation methods and data from the Medical Expenditure Panel Survey to compare nondisabled adults enrolled in Medicaid prior to the ACA with two other groups: adults who were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The nephrology community and related stakeholders should unite in a strategic effort to address the clinical, financial, and public policy issues that will enable the delivery of appropriate CKD care to low socioeconomic and other vulnerable patient populations 16 . The Affordable Care Act (ACA) has dramatically increased the number of low-income nonelderly adults eligible for insurance overage including Medicaid, 53 and may have favorable overarching consequences on mitigating prior disparities. A recent survey from Barcellos et al found that lower income persons (100–250% FPL) in comparison to higher income persons (≥400% FPL) were 31% less likely to score above the median on ACA knowledge, and 54% less likely to score above the median on health insurance knowledge suggesting low SES can adversely impact understanding of the ACA and may limit its success 54 .…”
Section: Resultsmentioning
confidence: 99%
“…The nephrology community and related stakeholders should unite in a strategic effort to address the clinical, financial, and public policy issues that will enable the delivery of appropriate CKD care to low socioeconomic and other vulnerable patient populations 16 . The Affordable Care Act (ACA) has dramatically increased the number of low-income nonelderly adults eligible for insurance overage including Medicaid, 53 and may have favorable overarching consequences on mitigating prior disparities. A recent survey from Barcellos et al found that lower income persons (100–250% FPL) in comparison to higher income persons (≥400% FPL) were 31% less likely to score above the median on ACA knowledge, and 54% less likely to score above the median on health insurance knowledge suggesting low SES can adversely impact understanding of the ACA and may limit its success 54 .…”
Section: Resultsmentioning
confidence: 99%
“…A major element of the Affordable Care Act is the expansion of Medicaid to cover more individuals, particularly childless adults, who historically have had limited access to Medicaid coverage (Hill et al, 2014;Price & Eibner, 2013). The Supreme Court ruled in 2012 in the National Federation of Independent Business v. Sebelius case that states can decline to expand Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of Affordable Care Act (ACA) for CKD are also substantial given the tremendous role that the nephrology community has played in piloting key ACA demonstration programs (40,41). Although the ACA has dramatically increased the number of low-income nonelderly adults eligible for insurance coverage including Medicaid (42), implementation of the ACA varies by state, which may limit its success (36,43). Public health policies implemented at the state level are likely to affect a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%